综合传动装置齿轮故障诊断研究 - 曾兴祥; 樊新海; 姚炽伟 (Jixie chuandong)
Basic principle of spectrum zooming and demodulating methods based on Morlet combined wavelets are introduced.Combining the two methods together,the detailed structure of spectrum by using zooming method is observed,and then the characteristic frequency of fault by using demodulating method is extracted.Practice shows that,this method can effectively diagnose the demodulating fault of integrated transmission gear.